Image Schemas in Diasporic Visual Discourse: Peripheral Voices in the Selected Photographs of Afghan Migrants Living in Pakistan - Sara Khan; Nadia Anwar (NUML Journal of Critical Inquiry)
This study explores the socio-cognitive dynamics of the photographic representation of Afghan Refugees residing in Pakistan. It aims to reveal counter discursivity present in the images of Afghan refugees and accentuate the visual nature of this counter discourse. Data sets taken for analysis consist of five photographs of Afghan refugees retrieved from the album collection of an international photographer Muhammad Muheisen. By adopting an interdisciplinary perspective based on three schools, i.e. Critical Discourse Studies, Social Semiotics and Cognitive Linguistics, the study proposed a Cognitive Grammar approach to traditional Transitivity Analysis. Cognitive transitivity analysis explored the discursive strategy of Structural Configuration by highlighting the cognitive systems such as image schemas, narrative structures and processes in both visual representations and textual taglines assigned to the images by the photographer. The findings of the study revealed the employment of CONTAINER, FORCE, SPACE, and SOURCE- PATH Schemas and dominant presence of agentive and transactional roles of Afghan refugees. The taglines of photographs revealed material processes dominating the discourse, thus, coinciding with agentive representation of Afghan refugees. The findings revealed that image schemas, narrative structures and processes, being embodied sources, preconceptual and mimetic structures, project Afghan photographic discourse as marginalized in the face of Pakistan’s Refugee Policies.